Сутність та значення профорієнтаційної роботи в системі підготовки кадрів для органів внутрішніх справ України - Клочко, А. М.; Klochko, A. M.; ORCID: http://orcid.org/ 0000-0002-6898-964X (Науковий вісник Академії муніципального управління. Серія: Право. – 2015. – Вип. 1, Ч. 1. – С. 163-168, 2015)
У статті розглянуто питання сутності та значення профорієнтаційної роботи в системі підготовки кадрів для органів внутрішніх справ України. Автор проаналізував наукові тлумачення терміну професійна орієнтація та запропонував своє розуміння цього терміну. У статті наведені та детально проаналізовані складові системи профорієнтації. Розглянуто завдання та значення профорієнтаційної роботи в системі підготовки кадрів для органів внутрішніх справ України.

Actuality is that with the executive branch given important organs of internal affairs of Ukraine, this is due to the recent performance of law enforcement functions. Proper and effective their work is the main task of the state. Decisive role in the performance of law-enforcement bodies of their tasks and functions played by staffing qualified and motivated employees. These and other examples, in our view, clearly indicate the important role of training for enforcement bodies of Ukraine for society and the state. With this in mind, takes the essence of relevance and importance of career guidance in training personnel for the internal affairs of Ukraine, which is the main purpose of this article. The continuation of scientific work on the mentioned issues is the article, the novelty of which is the essence and importance of career guidance in training personnel for the internal affairs of Ukraine carried out in the light of administrative law. Thus, to achieve the goal of this paper is planned through the study of administrative experience in scientific definition of regulatory consolidation and indicated categories, followed by the formulation of their own conclusions. A large number of professions, lack the necessary knowledge of the content of work in the world of professions, self difficulties each person his personal qualities make the task of choosing the right profession and reasonable construction of his working life for young people very difficult. Studies show that most personal professional plans are not feasible; consequently, there are lack of interest in work, profession change, the loss of faith in themselves. The article is to determine the nature and value of career guidance in training personnel for the internal affairs of Ukraine. To achieve this goal it is planned to address the following objectives: to determine the range of staffing and analyze their administrative and legal status. Also conclusions are that the system of vocational training for enforcement bodies of Ukraine - a set of interrelated measures applied relevant entity aimed to help young people in the choice of future profession - police officer, according to their abilities, desires and desired results. It includes professional information, professional consultation, professional selection, professional adaptation.

В статье рассмотрены вопросы сущности и значения профориентационной работы в системе подготовки кадров для органов внутренних дел Украины. Автор проанализировал научные толкования термина профессиональная ориентация и предложил свое понимание этого термина. В статье приведены и подробно проанализированы составляющие системы профориентации. Рассмотрены задачи и значение профориентационной работы в системе подготовки кадров для органов внутренних дел Украины.
Сущность и значение профориентационной работы в системе подготовки кадров для органов внутренних дел Украины
Nature and significance career guidance in training for internal affairs of Ukraine
Клочко А.М. Сутність та значення профорієнтаційної роботи в системі підготовки кадрів для органів внутрішніх справ України / Клочко А.М. // Науковий вісник Академії муніципального управління. Серія: Право. – 2015. – Вип. 1, Ч. 1. – С. 163-168.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Internal Affairs Agencies; органы внутренних дел; профорієнтаційна робота; профориентационная работа; vocational work; підготовка кадрів; подготовка кадров; personnel training